Segmenting Hungarian Consumers by Domestic Food Preferences Using an Extended TPB Model - Taralik, Krisztina; Novák, Tamás (Marketing & Menedzsment, 2025)
AIM OF THE PAPER Promoting domestic food consumption is a significant mission from both environmental and economic perspectives. To achieve the effectiveness of targeted marketing strategies promoting domestic food consumption, it is essential to understand domestic customers, identify homogeneous groups, and describe the characteristics of these groups. METHODOLOGY For data collection, a quantitative online questionnaire was used to interview 700 respondents representing the Hungarian population over 18. As a cluster-forming criterion, factors of the Theory of Planned Behavior were used, extended with the constructs of Environmental Concern and Collectivism. Demographic patterns were compared among the groups segmented and described based on psychological factors. MOST IMPORTANT RESULTS 3 segments were distinguished according to how important the respondents considered buying Hungarian food. In the group that considered this more important than the others, there was a higher proportion of females and respondents over 50. There were only trend-like differences in the composition of the segments in terms of type of settlement and region. At the same time, there was a statistically verifiable difference according to settlement types in terms of perceived social pressure, as well as regionally in terms of collectivism and environmental concern. RECOMMENDATIONS In those regions where the environmental concern of the respondents was lower, it may be worthwhile conducting a more intensive integrated campaign that targets the cognitive, affective, and conative aspects of environmental concerns at the same time. In more individualistic subcultures, the illumination of individual interests arising from the purchase of domestic food products should be given a greater role, while in more collectivist subcultures, the role of reference groups should be considered more strongly.